Network disruption detected in TZ (Tanzania) - Voidly (2026)
CRITICAL severity disruption detected in Tanzania. Confidence: 70%. Data sourced from CensoredPlanet, IODA.
Network Disruption Incident ID: TZ-2026-0003
Keywords: internet disruption; TZ; disruption; critical